2020
DOI: 10.1177/0886260520967132
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Impacts of Sexual Violence Against Men and Boys in Conflict and Displacement: A Multicountry Exploratory Study

Abstract: Evidence of sexual violence against men and boys in many conflict-affected settings is increasingly recognized. Yet relatively little is currently known about the varied forms, sites, and impacts of this violence. Further, scant research on sexual violence against men and boys in displacement contexts has been undertaken to date. To begin to address these knowledge gaps, we undertook a multicountry, qualitative, exploratory study to gain insights into these issues. Study settings and populations were Rohingya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 32 publications
0
29
0
20
Order By: Relevance
“…For example, forced witnessing of sexual violence against othersan often overlooked type of sexual violencewas reportedly common in conflicts in Bosnia-Herzegovina, eastern DRC and Myanmar, among others (Touquet, forthcoming;Chynoweth, 2019a;Promundo, 2013). Genital violence was commonplace against men and boys in conflicts in Croatia, Bosnia-Herzegovina and Kenya, and has been reported in other settings (Lončar et al, 2010;Carlson, 2006;Auchter, 2017;Myrttinen, 2018;Chynoweth et al, 2020b). In conflict-affected areas in eastern DRC, a population-based study found that 19.6 per cent of men/ boy survivors disclosed suffering sexual slavery, while 5 per cent reported being forced to perform a sexual act (Johnson et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, forced witnessing of sexual violence against othersan often overlooked type of sexual violencewas reportedly common in conflicts in Bosnia-Herzegovina, eastern DRC and Myanmar, among others (Touquet, forthcoming;Chynoweth, 2019a;Promundo, 2013). Genital violence was commonplace against men and boys in conflicts in Croatia, Bosnia-Herzegovina and Kenya, and has been reported in other settings (Lončar et al, 2010;Carlson, 2006;Auchter, 2017;Myrttinen, 2018;Chynoweth et al, 2020b). In conflict-affected areas in eastern DRC, a population-based study found that 19.6 per cent of men/ boy survivors disclosed suffering sexual slavery, while 5 per cent reported being forced to perform a sexual act (Johnson et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Sexual violence against men and boys in armed conflict has garnered increasing attention over the past decade. 1 A growing body of evidence demonstrates that sexual violence against men and boys is perpetrated in many conflicts and that men and boys are also subject to sexual violence during displacement (Chynoweth et al, 2020b;Féron, 2018;Hossain et al, 2014;Johnson et al, 2008Johnson et al, , 2010Schulz, 2020;Schulz and Touquet, 2020;Touquet, 2018a). The notion that little to no research exists is no longer valid.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations